Diplomacy of Semarang City Government through International Human Rights Festival 2021-2022 - Hartati, Anna Yulia; Purwono, Andi; Riyanto, Agus; Adiba, Amanda Noor (RMPI-BRIN, 2024)
Discourses on the role and responsibility of regional government in protecting and fulfilling human rights have drawn serious attention of international community. On the international level, the concept of human rights cities (Human Rights cities or regions) was introduced to promote more active engagement and empowerment in developing and advancing its respective regions. This discourse is facilitated by involvement and active participation of sub-national government (regional government or city government) in responding international issues. Studies on the involvement of cities in diplomacy has been conducted, yet none of those discussed the cities’ engagement in international human rights issues. Semarang city has been selected as the host of International Human Rights Festival in 2021. The purpose of this research is to find out the motivation of Semarang City Government in becoming the host of International Human Rights Festival. Theoretical framework for this research is city diplomacy and human cities rights concept. The method used in this research is qualitative, data collected through interview, observation and document study. The finding of this research shows that the purpose of Semarang city government in becoming the host of International Human Rights Festival in 2021 is to promote Semarang city’s image, advance international relations, to improve awarness of its people on human rights issues and promoting tourism.